Anxiety an extraction of third molars in Turkish patients - GARİP, HASAN (CHURCHILL LIVINGSTONE, 2004)
Preoperative anxiety is widespread and adversely affects a patient's physical and psychological outcome. Extraction of third molars is common, and many patients complain of anxiety and emotional disturbance. We assessed the anxiety of patients in Turkey before extraction of third molars. A total of 120 patients were admitted for removal of one or more third molars under local anaesthesia. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) and Spielberger's State Trait Anxiety Inventory (STAI) were used to evaluate anxiety. The results showed that women were significantly more anxious than men; women who had not had a previous operation were more anxious than other women; there was no difference in the anxiety scores of patients who had previously had a local anaesthetic and those who had not; there were no differences in anxiety as measured by trait scores; patients who wanted a lot of information were more anxious. (C) 2004 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: molar surgery; preoperative anxiety; psychological; AMSTERDAM PREOPERATIVE ANXIETY; INFORMATION SCALE APAIS; SURGERY; REMOVAL; DAMAGE